2010
DOI: 10.1128/aac.01557-09
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Listeria monocytogenes Strains Isolated from Humans in France

Abstract: Susceptibility to antibiotics of 4,816 clinical L. monocytogenes strains isolated since 1926 was studied, and the temporal evolution of susceptibility to antibiotics was analyzed through several decades. The mechanisms of resistance in each resistant strain were studied. The prevalence of resistant strains was estimated at 1.27% among isolates from humans. Resistance to tetracyclines؉ and fluoroquinolones was more common and has recently emerged. Although acquired resistance in clinical L. monocytogenes did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
169
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(195 citation statements)
references
References 39 publications
15
169
3
8
Order By: Relevance
“…has been studied in various food, environmental and clinical settings (Bertrand et al, 2005;Morvan et al, 2010;Granier et al, 2011;Jamali et al, 2015). Listeria monocytogenes has generally been shown to be more susceptible to antimicrobial agents then other species in the genus.…”
Section: Resultsmentioning
confidence: 99%
“…has been studied in various food, environmental and clinical settings (Bertrand et al, 2005;Morvan et al, 2010;Granier et al, 2011;Jamali et al, 2015). Listeria monocytogenes has generally been shown to be more susceptible to antimicrobial agents then other species in the genus.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand B. cereus and L. monocytogens are also Gram-positive bacteria like S. aureus but they are more resistant to carvacrol microemulsion Table 2 . That could be due to the spore forming nature of B. cereus or the presence of specific antimicrobial drug resistant genes in this microorganism 57 and in L. monocytogens 58,59 which are not present in S. aureus. Table 3 showed that formulation of carvacrol in microemulsion using the cationic surfactant CPC had significantly higher antibacterial activity than that formulated with the non-ionic T20.…”
Section: Antimicrobial Activity Of Carvacrol Microemulsionmentioning
confidence: 99%
“…It appears that virtually the same profile has been identified over the years and in different countries. In relation to tetracycline, this research highlighted the extreme sensitivity of the 68 strains to this drug, contrasting with the emergence of clinical strains resistant to tetracycline, related to the gene tetM 5,22,23 .…”
Section: Discussionmentioning
confidence: 99%